1999
DOI: 10.1161/01.str.30.4.841
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque, Intima Media Thickness, Cardiovascular Risk Factors, and Prevalent Cardiovascular Disease in Men and Women

Abstract: Background and Purpose-B-mode ultrasound is a noninvasive method of examining the walls of peripheral arteries and provides measures of the intima-media thickness (IMT) at various sites (common carotid artery, bifurcation, internal carotid artery) and of plaques that may indicate early presymptomatic disease. The reported associations between cardiovascular risk factors, clinical disease, IMT, and plaques are inconsistent. We sought to clarify these relationships in a large, representative sample of men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
488
11
35

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(588 citation statements)
references
References 54 publications
41
488
11
35
Order By: Relevance
“…This is in accordance with the previous results concerning carotid arteries. 5,12,14 We did not find any previous studies evaluating only the possible association between SBP and plaques in either femoral arteries or aorta. Simon et al 13 studied the risk factors for plaques in carotid, aortic and femoral arteries and showed that the SBP of the study subjects increased with an increasing number of arteries with plaques.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This is in accordance with the previous results concerning carotid arteries. 5,12,14 We did not find any previous studies evaluating only the possible association between SBP and plaques in either femoral arteries or aorta. Simon et al 13 studied the risk factors for plaques in carotid, aortic and femoral arteries and showed that the SBP of the study subjects increased with an increasing number of arteries with plaques.…”
Section: Discussionmentioning
confidence: 76%
“…33 Except for high SBP, high MBP was also associated with plaques in this study population. Apart from BP, male gender 5,12,28,30 and smoking [13][14]30 are well-established risk factors for atheromatous plaques. Carotid atherosclerosis measured by ultrasound appears to be associated with coronary artery disease 34 and to predict myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients with stroke have increased carotid IMT compared with controls. 10 Recent prospective studies have also demonstrated that individuals with a greater degree of carotid atherosclerosis are at an increased risk of stroke. 11,12 Our study has confirmed that patients with stroke have a greater degree of carotid atherosclerosis compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying cause of these cardiovascular disease subgroups is atherosclerosis, a complex multifactorial disorder of the arteries initiated by endothelial dysfunction, inflammation, and dyslipidemia 2, 3. Subclinical measures of atherosclerosis include common carotid artery intima‐media thickness (CCA‐IMT) and carotid atherosclerotic plaques, both of which have been shown to predict myocardial infarction and stroke 4, 5, 6…”
Section: Introductionmentioning
confidence: 99%